2012
DOI: 10.3997/1873-0604.2012051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GPR and unilateral NMR for water content measurements in a laboratory scale experiment

Abstract: Several factors affect antenna‐soil coupling in a Ground Penetrating Radar (GPR) survey, like surface roughness, lithology, lateral heterogeneities, vegetation, antenna height from the surface and water content. Among them, lithology and water content have a direct effect on the bulk electromagnetic properties of the material under investigation. It has been recently pointed out that the wavelet of the early‐time portion of a radar signal is correlated to the shallow subsurface dielectric properties of a mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…The waveform amplitude has an inverse linear dependence on the permittivity. In particular, [14] and [15] confirmed that because the first arrival of the GPR signals is strongly dependent on variations in the shallow subsurface permittivity, the signal to noise ratio can be maximized by minimizing the interference from reflections caused by shallow interfaces.…”
Section: Methodsmentioning
confidence: 50%
“…The waveform amplitude has an inverse linear dependence on the permittivity. In particular, [14] and [15] confirmed that because the first arrival of the GPR signals is strongly dependent on variations in the shallow subsurface permittivity, the signal to noise ratio can be maximized by minimizing the interference from reflections caused by shallow interfaces.…”
Section: Methodsmentioning
confidence: 50%
“…2). The choice of analysing the first half-cycle comes from previous experimental and theoretical studies [1,2], where it was found that the first half-cycle is the part of the signal which exhibits the best correlation with the soil dielectric properties, maximizing the signal-to-noise ratio and minimizing interference from reflections caused by shallow interfaces. To determine the uncertainty associated with the GPR envelope amplitudes, we acquired a total of 1000 traces for each measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The TDR-derived average permittivity was also compared with the GPR-derived average permittivity, which was determined from the two-way travel (TWT) time according to standard procedures. Specifically, to extract the permittivity information from the GPR data, we have calculated the cross-correlation function between the direct and reflected wavelet envelopes [2,4], determining a permittivity average value of ε r_GPR =29±2.…”
Section: Experimental Setup and Data Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations